Combustion performance in a cavity-based combustor under subatmospheric pressure. (15th October 2021) - Zhu, Zhixin; Huang, Yakun; Zhang, Huangwei; He, Xiaomin
Highlights: A cavity-based augmentor for subatmospheric combustion is designed. Spray ignition and blowout processes under low pressure are presented. Flame stability limits and combustion efficiency are plotted at 0.03–0.06 MPa. Fuel distribution between the piloted cavity and mainstream is discussed. Experimental results help to improve the low-pressure combustion performance. Abstract: Combustion performance and flame stabilization mechanism of the flameholder under the subatmospheric pressure are the foundation for the design of high-altitude operating aircraft. An experimental cavity-based combustor was developed to explore the combustion performance in low pressure. Four low pressures of 0.03, 0.04, 0.05 and 0.06 MPa were validated to investigate the effect of inlet pressure on the flame stability limits, lean ignition and blowout process, combustion efficiency, and outlet temperature profiles. A unique lean spark ignition process was discovered at 0.03 MPa that the flame downstream of the V-type flameholder promotes the formation of the piloted flame in the cavity. Results indicate that the pressure reduction decreases the spray flame propagation, subsequently weakening flame stability and combustion efficiency. With the inlet pressure decreases, the pilot fuel injected into the cavity still maintains effective combustion, while the declining combustion is achieved in the mainstream fuel. This phenomenon suggests that increasing the pilot fuel proportion in the combustion chamber will enhance the combustion in ultra-low pressure.